A Schulman is increasing colour masterbatch capacity in Europe. Issue 5 (May 2017) - Unknown
Abstract : International producer of masterbatches, high-performance plastic compounds and resins A. Schulman Inc plans to increase its production capacity for colour masterbatches in Europe. Three additional extrusion lines are to be installed, one each at its plants in Hungary, Italy and Poland. The expansion is in response to increased market demand, the company reports.